Azadirachtin-Based Insecticide: Overview, Risk Assessments, and Future Directions - Kilani-Morakchi, Samira; Morakchi-Goudjil, Houda; Sifi, Karima (Frontiers in Agronomy, 2021)
In the context of the major crop losses, pesticides will continue to play a key role in pest management practice in absence of practical and efficient alternatives. However, increasing awareness regarding environmental and human health impacts of conventional pesticides as well as the development of resistance and cross resistance reduced their availability and promoted the search for alternative control strategies and reduced risk pesticides. Among the various alternatives, a drastic re-emergence of interest in the use of plant-derived compounds, called allelochemicals, was noted and demand for organic product is rising. Currently, azadirachtin, a tetranortriterpenoid derived from neem seed of the Indian neem tree (Azadirachta indica A. Juss (Meliaceae), is one of the prominent biopesticides commercialized and remains the most successful botanical pesticide in agricultural use worldwide. Azadirachtin is a powerful antifeedant and insect growth disruptor with exceptional low residual power and low toxicity to biocontrol agents, predators and parasitoids. This review summarize the state of the art on key azadirachtin insecticidal activities and risk assessment, identify knowledge gaps that could serve as the basis for future research direction and highlight limitation in agricultural use and the development of novel strategies by the use of nanotechnology to control its release rate and improve its stability and sustainability.